2018
DOI: 10.1016/j.kontakt.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among interventions and health literacy outcomes for sub-populations: A data-driven approach

Abstract: The goals of this study were to examine relationships among health literacy and outcomes for sub-populations identified within a large, multi-dimensional Omaha System dataset. Specific aims were to extract sub-populations from the data using Latent Class Analysis (LCA); and quantify the change in knowledge score from pre-to post-intervention for common sub-populations. Design: Data-driven retrospective study using statistical modeling methods. Sample: A set of admission and discharge cases, captured in the Oma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The terms and definitions of standardized nursing terminologies such as the Omaha System are a granular set of concepts that together describe a comprehensive, holistic conceptual framework for health (Martin, 2005). These terms and definitions may be used to operationally define and represent more complex concepts such as the social determinants of health, health literacy, and wellbeing (Monsen, 2018; Monsen et al, 2015; Monsen et al, 2017; Michalowski et al, 2018). Conducting advanced exploratory analyses using data generated by standardized nursing terminologies is possible because this rigorous definitional work was completed a priori (Martin, 2005; Monsen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The terms and definitions of standardized nursing terminologies such as the Omaha System are a granular set of concepts that together describe a comprehensive, holistic conceptual framework for health (Martin, 2005). These terms and definitions may be used to operationally define and represent more complex concepts such as the social determinants of health, health literacy, and wellbeing (Monsen, 2018; Monsen et al, 2015; Monsen et al, 2017; Michalowski et al, 2018). Conducting advanced exploratory analyses using data generated by standardized nursing terminologies is possible because this rigorous definitional work was completed a priori (Martin, 2005; Monsen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Additional methods, such as algorithm development and AI, have potential to identify high‐risk clients who would benefit from interventions at the time of admission would be beneficial for PHN home visiting services. Latent class analysis using the Omaha System have proven useful in identifying clinically relevant groups and corresponding interventions from PHN documentation data (Michalowski et al., 2018; Monsen et al., 2010; Van Laarhoven et al., 2020). A latent class analysis of clients with mental health signs/symptoms and PHN interventions demonstrated that having more mental health signs or symptoms was positively associated with the number of interventions administered by the PHNs, indicating that nurses are identifying those at risk and tailoring interventions accordingly (Van Laarhoven et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Informatics methods, such as clinical decisions support, have produced useful insight for PHN care (Lu et al, 2022) (Michalowski et al, 2018;Monsen et al, 2010;Van Laarhoven et al, 2020)…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it is pertinent that novel techniques that support precision health promotion are implemented to increase vaccination uptake behaviors. The application of digital educational interventions for personalized health coaching can generate customized recommendations in a case-by-case manner, improve health literacy and knowledge acquisition, optimize information-seeking behavior, promote healthy behavior (eg, HPV vaccine uptake; sexually transmitted infection [STI], HPV, or genital warts testing; and cervical cancer screening), and lead to better population health outcomes (eg, HPV-associated cancer prevention) [ 13 , 14 ]. Advances in artificial intelligence (AI) and digital technologies have revolutionized several applications in health care [ 15 ], promoting and enhancing personalized patient care.…”
Section: Introductionmentioning
confidence: 99%